Electrospinning of magnetic cellulose tris‐(4‐methylbenzoate) microparticles for enantioselective adsorption of racemic drug. Issue 14 (23rd May 2016) - Huang, Tengjun; Song, Peipei; Jiang, Li; Peng, Yan; Feng, Shun; Wang, Jide
Abstract : In this work, we introduce electrospinning to prepare magnetic enantioselective material for the first time. Multianalytical tools were used to characterize the resulted magnetic cellulose tris‐(4‐methylbenzoate) particles including transmission electron microscopy, SEM, FTIR spectroscopy, thermogravimetric analysis, X‐ray diffractometer. Under the optimum conditions, the resulted particles were well‐shaped sphere with a diameter range of 800 nm to 2 μm and high magnetic sensitivity. The enantioselectivity of the adsorbents was evaluated using racemic ibuprofen as a model drug; an e.e. value of −4.78% (where e.e. is enantiomeric excess) was achieved in a single adsorption stage. We hope that our finding provides an efficient and economical procedure for the preparation of magnetic enantioselective materials with high selectivity and reproducibility.